Peru: Assessing its strong macroeconomic performance through labor market indicators - Larios Meoño, J. Fernando (2018)
This paper analyzes Peru's structural change in the last 16 years (2001-2016) through the labor market indicators' lenses. The paper's assessment of the past 16 years is somewhat bitter sweet. On the positive side, there has been a major reallocation of labor resources away from agriculture into the rest of the economy without any major disruption in wages, unemployment levels and inflation as it had been in previous resource booms. Yet, most employment created during that period-notably in commerce and transport and communication-has been in jobs paying wages that are roughly equal or below the economy's average. Wages in these sectors have been increasing broadly in line with productivity growth, thus keeping unit labor costs (ULCs) largely unchanged despite underlying inflation. The inertia of ULCs growth should have, in principle, spurred a tighter growth of households' real income, consumption and savings than otherwise. The findings from this paper are consistent with the world trend towards precarious labor conditions, especially for those youngsters entering the labor force. In a way, the emerging gig economy in the United States and other industrialized countries has been the Peruvian labor market's reality for decades to date. From a cyclical condition, widespread underemployment has become a structural condition in the country's economic reality. Policies to secure adequate health care and pension benefits are a latent concern for the country authorities and will require bold decisions in devising and implementing lasting changes for the benefit of the society, overall.